GANTI RUGI SEBAGAI UPAYA PERLINDUNGAN HAK KORBAN KEJAHATAN PERSPEKTIF POLITIK HUKUM PIDANA - Bennaris Kaban; Mahmud Mulyadi; Adi Mansar (Universitas Labuhanbatu, 2023)
Legal protection for crime victims in positive law in Indonesia, it still abstract or indirect protection, it is said that because a criminal act according to positive law dosen’t seen as as an act of attacking a person’s public interest but only seen as a violation of norms or the rule of law. Therefore in its development criminal law enforcement in the future must pay more attention to the rights of victims, including by providing compensation.To explore this problem, the formulation of the problem in this study: How is the posisition and protection of crime victims in positive criminal law in Indonesia? What is the prospect of criminal compensation in the poitics of criminal law in Indonesia? The research method in relation of this thesis includes tha type of normative legal research based on secondary data. This study using statute approach and conceptual approach. The result of this thesis research show: (1) Legal protection for victims of crime in positive law in Indonesia still limited to stipulated in special laws, especially related to provision of compensation for victims of crime while general crimes of crimes victims are not protected concretely in KUHP (criminal code). (2) Criminal compensation has good prospect, good in law enforcement, because it places victims of crime of legal subject vho must be protected in order to achieves legal goals, namely certainty, justice, and benefit.Keywords : compensation, legal protection, crime victims